POLA ASUH ORANG TUA DALAM KELUARGA - Lola Anjelia; Zhelin Florencia Aurora; Siti Fadila; Evryeni Jusmadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Parenting patterns are one of the important aspects in family life that greatly influence the formation of children’s character, personality, and development. The family becomes the first environment for children to learn about values, norms, attitudes, and behavior in everyday life. In this process, parents have the main role as the first and primary educators for children through attention, affection, supervision, guidance, and discipline. Different parenting styles applied by parents can have different impacts on children’s emotional, social, moral, and intellectual development. This article aims to explain the meaning of parenting in the family, the types of parenting styles, the factors that influence them, and the impact of parenting on child development. The method used in writing this article is a literature study by reviewing various sources such as books, journals, and scientific references related to parenting in the family. The results of the discussion show that democratic parenting is the most effective parenting style because it can create a harmonious relationship between parents and children, increase children’s self-confidence, and support children’s development optimally. Therefore, parents are expected to apply appropriate parenting styles so that children can grow into independent, responsible, disciplined individuals with good morals.